Leber's optic neuropathy: clinical and visual evoked response studies in asymptomatic and symptomatic members of a 4-generation family. Issue 10 (October 1980) - Livingstone, I R; Mastaglia, F L; Howe, J W; Aherne, G E
Abstract : A clinical and neuro-ophthalmological examination using tests of visual acuity, quantitative visual field analysis, tests of colour discrimination, ophthalmoscopy, and pattern visual evoked responses was performed on 2 symptomatic and 16 asymptomatic members of a family with Leber's optic neuropathy. The visual evoked responses were abnormal in the 2 clinically affected males and in 1 asymptomatic male. Tests of colour discrimination with Ishihara plates, the Farnsworth-Munsell 100 hue test, and the Nagel anomaloscope revealed abnormalities in 8 asymptomatic family members, with the Farnsworth-Munsell test proving to be the most sensitive to mild abnormalities of colour discrimination. The occurrence of detectable neuro-ophthalmological abnormalities within this family is in keeping with the expected pattern of transmission of Leber's optic neuropathy. The significance of detection of presymptomatically affected cases and asymptomatic carriers is discussed.